1987
DOI: 10.3168/jds.s0022-0302(87)80030-9
|View full text |Cite
|
Sign up to set email alerts
|

Somatotropin and Lactation

Abstract: Somatotropin, which can now be produced by biotechnology, could have an enormous impact on the dairy industry. Milk yield has been increased up to 40% with daily injections of somatotropin. Cows adjust their nutrient intake to support this increase. Somatotropin does not adversely affect cows' health, although all studies to date have been for less than one complete lactation. The search for a single biochemical or physiological event to account for the effects of somatotropin on milk production is elusive. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
87
0
13

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(111 citation statements)
references
References 53 publications
11
87
0
13
Order By: Relevance
“…Similar results were reported in 15 commercial dairy herds given bST, with responses ranging from 11 to 29% for milk yield (Thomas et al, 1991). Peel and Bauman (1987) reported that milk yield slowly increases the first few days after bST treatment, with maximum yield at about the sixth day after administration. Jordan et al (1991) reported that milk and protein yields increased by 18.8 and 3.3%, respectively, for high-producing cows, with no effect on somatic cell score (SCS).…”
Section: Introductionsupporting
confidence: 72%
“…Similar results were reported in 15 commercial dairy herds given bST, with responses ranging from 11 to 29% for milk yield (Thomas et al, 1991). Peel and Bauman (1987) reported that milk yield slowly increases the first few days after bST treatment, with maximum yield at about the sixth day after administration. Jordan et al (1991) reported that milk and protein yields increased by 18.8 and 3.3%, respectively, for high-producing cows, with no effect on somatic cell score (SCS).…”
Section: Introductionsupporting
confidence: 72%
“…Si la nature de l'aliment est l'un des facteurs de variation de la production et de la qualité du lait, le recours à la somatotropine bovine recombinée (rbST) peut être considérée comme une des techniques d'intensification de la production laitière (Cordonnier, 1989). L'influence de la rbST sur la production laitière a été largement démontrée et a fait l'objet depuis plusieurs années de très nombreux travaux (Peel et Bauman, 1987 ;Chilliard, 1988 ;Dell'Orto et Savoini, 1991 ;Bauman, 1992 ;Burton et al, 1994) (Chilliard, 1988). L'augmentation de la production de matières protéiques a été trouvée aussi par Stelwagen et al (1993).…”
Section: Introductionunclassified
“…Furthermore, exogenous GH increases the number of follicles in lactating cows [7] and heifers [8,9]. The small follicles induced by GH appear to be fully rowth hormone (GH) regulates growth and differentiation of various cell types and controls G anabolism and metabolism of organs and tissues [1,2]. Although there is considerable evidence that the ovary is one of the sites of GH binding and action [3], its exact role in the control of reproduc-functional since the treatment of cattle with pregnant mare serum gonadotropin following GH resulted in significant increase of the number of ovulations and the number of embryos recovered [10].…”
mentioning
confidence: 99%